PENGARUH MODEL MASTERY LEARNING BERBANTUAN VIDEO TERHADAP HASIL BELAJAR GEOGRAFI DI SMA N 4 BUKITTINGGI - Febriany, Suci; Anwar, Syafri (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to determine whether there is an effect of video-assisted mastery learning model on geography learning outcomes at SMA N 4 Bukittinggi. This research uses a quantitative approach with the type of quasy experiment. The population in this study is XI grade geography students, the total number is 80 people. Research sampling, using purposive sampling technique selected two classes, namely class XI Geo B as an experimental class, and class XI Geo D as a control class and each class amounted to 26 students. To determine the effect of learning, pretest and posttest were conducted in both classes. Data analysis techniques used are normality test, homogeneity test, t test and N-Gain test. The results of the study found that there was an effect of mastery learning model assisted by video on students' geography learning outcomes. Proven by the results of the t test based on the pretest and posttest results of the control and experimental classes that tcount> ttable is 5.239> 1.676. So it is concluded that there is an effect of video-assisted mastery learning model on geography learning outcomes at SMA N 4 Bukittinggi.